The investigation of possibilities to use open source virtual learning environments in general schools - Jasutienė, Eglė; Markauskaitė, Lina (Lietuvos matematikos rinkinys, 2004)
The paper analyses possibilities to adapt and introduce open source Virtual Learning Environment (VLE) in general schools of Lithuania. First, it looks at general functions of VLE and defines its generic model. After that, the paper analyses four specific aspects of general education in Lithuania: National Curricula and Standards, age range of learners, compulsory attendance of a school, and the level of ICT development in schools. On that basis, it decides, which VLE’s functional requirements are the most essential. Later, the paper investigates and compares the main features of eight worldwide popular open source VLEs. It looks, how the VLEs mach the needs of Lithuanian schools. It concludes that Moodle and Caroline software fit the best.